Clinical experience with trisomies 18 and 13. - Hodes, M E (1978)
The clinical, cytogenetic, dermatoglyphic, and postmortem observations of the 29 cases of trisomy 18 and 19 cases of trisomy 13 seen in the Department of Medical Genetics from 1963-76 are summarised. Chromosomes were studied in all and 30 were banded. One patient had tertiary trisomy 18 and 8 had translocations of chromosome 13. The features of these patients are described and the syndromes compared with each other and summaries found in the literature.